Update on Surgical Management of Pediatric Urolithiasis - Sultan, Sajid; Aba Umer, Sadaf; Ahmed, Bashir; Naqvi, Syed Ali Anwar; Rizvi, Syed Adibul Hasan (Frontiers in Pediatrics, 2019)
Urolithiasis has always been a fascinating disease, even more so in children. There are many intriguing facets to this pathology. This article is a non¬-systematic review to provide an update on the surgical management of paediatric urolithiasis. It highlights the pros and cons of various minimally invasive surgical options such as ESWL,RIRS ,PCNL, laparoscopy and robotics. This article also describes the various intracorporeal disintegration technologies available to fragment the stone, including the newer advancements in laser technology. It also emphasizes the cost considerations especially with the reference to the emerging economies. Thus this manuscript guides how to select the least invasive option for an individual patient, considering age and gender; stone size, location and composition; facilities and expertise available.